Universities and Social Cohesion in the European Union - Bastedo, Michael (International Higher Education, 2008)
It has become conventional wisdom in recent years that Europe faces a daunting challenge of social cohesion in the face of increasingly hostile and radical Islamic immigrants residing in European cities. It has thus become a goal in the European Union to increase social cohesion using state programs and resources, universities among them. From a governance perspective, the top-down approach to social cohesion does not seem likely to succeed beyond its symbolic value. Instead, we must rethink governance from the bottom up.